Glycemic metrics in Japanese isCGM users – Analysis by diabetes type and therapy - Wataru Ogawa; Tatsuhiko Urakami; Takashi Kadowaki; Kalvin Kao; Laura Brandner; Kenichiro Shimizu; Timothy C. Dunn (Journal of Diabetes Investigation, 2024)
ABSTRACT Aims/Introduction The FreeStyle Libre (FSL) intermittently scanned continuous glucose monitoring (isCGM) system continually measures interstitial glucose levels and provides the data to users in numerical and graphical formats that guide users in their daily diabetes self‐management. Although numerous studies have demonstrated the glycemic benefits of FSL in pediatric and adult populations, few studies have characterized FSL use specifically by Japanese adults with type 1 or 2 diabetes. We utilized established CGM metrics to assess glycemic control in a large cohort of Japanese adults with type 1 and 2 diabetes. Materials and Methods A total of 3,463 anonymized FSL users provided categorization into one of four therapy groups of interest: type 1 diabetes (n = 1,768), type 2 diabetes‐multiple daily injections (MDI) (n = 612), type 2 diabetes‐basal (BOI) (n = 343), and type 2 diabetes‐non‐insulin (NIT) (n = 740). Established CGM metrics were used to assess glycemic control. Results All study groups showed relatively good glycemic control. Type 1 diabetes users showed the highest glucose variability (SD, 61 mg/dL; and %CV, 40%), above the established target level (%CV ≤ 36%). type 2 diabetes‐MDI and type 2 diabetes‐BOI users had similar levels of glucose variability (both within target). Type 2 diabetes‐NIT users had the highest mean % time in range (TIR) (84.3%) and largest percentage of users that met the target of %TIR > 70% (87.4%). In contrast, type 1 diabetes users had the lowest mean %TIR (62.6%) and the lowest percentage meeting the established %TIR target (30.5%). Conclusions By utilizing CGM devices in daily diabetes care, both healthcare professionals and patients can monitor glycemic excursions and gain insights into their historical glucose control patterns.